Prawa ucznia: wiedza, opinie i doświadczenia gimnazjalistów. Badania własne - Dyrdół, Małgorzata (Kultura-Społeczeństwo-Edukacja, 2013)
This article reveals the findings of research on students’s rights. The research was carried out twice: in 2006 and in 2012 among lower secondary school students. 223 participants from five schools have filled in the questionnaire form. This descriptive research show student’s knowledge, opinion and experience on how their rights respected In their schools.